Diacylglycerol Oil: Property and Production - กู่พงษ์ศักดิ์ ศศิกานต์; ฤาชาฤทธิ์ ปัทมา (KKU Science Journal, 2014)
Recent studies on the nutritional properties and dietary effects of DAG oils, which contain at least 80 wt% DAG, have demonstrated some beneficial effects. Studies on animal and human have revealed a decrease in accumulation of TAG in body fat and liver after intake of DAG oil. The production of DAG oils can be classified by using different catalyst and reaction types. Enzymatic-catalyzed reaction provides several advantages over chemical production using base or inorganic catalysts at high temperature. A mild condition can produce desired high-DAG yield and purity. The most important method for production of DAG involves three reactions: esterification, glycerolysis, and partial hydrolysis followed by esterification. In addition, the separation and purification processes can help to increase DAG yield after the DAG-synthesis reaction.